Vassily Kandinsky - Bill, Max, 1908-1994.; Giedion-Welcker, Carola (Barcelona : Polı́grafa ; Hove : Roundhouse [distributor], 2009)
- Kandinsky the educator / Max Bill -## Kandinsky the theoretician / Carola Giedion-Welcker -## Formative influences -## Developments in Munich -## Abandoning representation -## Non-objective painting -## The folkloric imagination -## A more rigorous style -## Point and line to plane -## A new freedom.
boek
Keywords: Kandinsky, Wassily; Kandinsky, Wassily